0=x+5

We need to get x by itself so -5 from both sides of your equation:

0-5=x+5-5

Note how this now gets x by itself

`therefore` -5=x

To check substitute your answer into your original equation so instead of 0=x+5, you will substitute x with -5

0=-5+5

0=0

This statement...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

0=x+5

We need to get x by itself so -5 from both sides of your equation:

0-5=x+5-5

Note how this now gets x by itself

`therefore` -5=x

To check substitute your answer into your original equation so instead of 0=x+5, you will substitute x with -5

0=-5+5

0=0

This statement is true because 0=0